Projecting the Global Potential Distribution of Cydia pomonella (Lepidoptera: Tortricidae) Under Historical and RCP4.5 Climate Scenarios. Issue 2 (12th April 2021) - Guo, Siwei; Ge, Xuezhen; Zou, Ya; Zhou, Yuting; Wang, Tao; Zong, Shixiang
Abstract: The codling moth Cydia pomonella (L.) (Lepidoptera: Tortricidae) is a destructive pest of apple (Malus domestica (Rosales: Rosaceae)), pear (Pyrus spp. (Rosales: Rosaceae)), and other pome tree fruits; outbreaks cause significant ecological and economic losses. In this study, we used CLIMEX model to predict and evaluate the global risk of C. pomonella based on historical climate data (1989–2018) and simulated future climate data (2071–2100) under the RCP4.5 scenarios. Cydia pomonella exhibited a wide distribution under both historical and future climate conditions. Climate change is predicted to expand the northern boundary of the potential distribution from approximately 60°N to 75°N. Temperature was the most dominant factor in climatic suitability for the pest. Combinations of multiple meteorological factors (relative humidity and precipitation) associated with a failure to break diapause in certain regions also affect suitability, particularly in northern South America and central Africa. Irrigation only had a slight impact on species favorability in some areas. The projections established in our study present insight into the global potential suitability of C. pomonella under climate change scenarios by the end of the 21st century. Farmers should be aware of the risk associated with the pest based on the results, which would provide guidance for quarantine agencies and trade negotiators worldwide.